Atmospheric Corrosion of Mg Alloy AZ91D Fabricated by a Semi-Solid Casting Technique: The Influence of Microstructure. Issue 7 (1st January 2015) - Esmaily, M.; Mortazavi, N.; Svensson, J. E.; Halvarsson, M.; Blücher, D. B.; Jarfors, A. E. W.; Wessén, M.; Johansson, L. G.
Abstract : The atmospheric corrosion behavior of alloy AZ91D produced by a semi-solid metal (SSM) technique and by conventional high pressure die casting (HPDC) was investigated for up to 1176 hours in the laboratory. Alloy AZ91D in the SSM state was fabricated using a rheocasting (RC) technique in which the slurry was prepared by the RheoMetal process. Exposures were performed in 95% RH air at 22 and 4°C. The RC alloy AZ91D exhibited significantly better corrosion resistance than the HPDC material at two temperatures studied. The effect of casting technology on corrosion is explained in terms of the microstructural differences between the materials. For example, the larger number density of cathodic β phase particles in the HPDC material initially causes relatively rapid corrosion compared to the RC material. During later stages of corrosion, the more network-like β phase particles in the RC alloy act as a corrosion barrier, further improving the relative corrosion resistance of the RC material.